Perundungan Dalam Drama The Glory Part 1: Kajian Pragmatik - Ittasaqa Maharani; Mei Solikhatul Latifakh; Salsa Rizkia Nurlaela; Anre Almanadaa; Asep Purwo Yudi Utomo; Didi Pramono; Rossi Galih Kesuma (Lembaga Pengembangan Kinerja Dosen, 2024)
Perlocutionary speech is a speech that the deliverance is intended to influence the speech partners. In this research, an analysis of the form of perlocutionary speech contained in the drama